A debreceni kitüntetéses doktoravatások története (1912–2012) - Kántor, Sándorné (Gerundium, 2013)
A HISTORY OF THE HONOUR DOCTORAL AWARDING CEREMONY IN DEBRECEN (1912–2012). his factually substantiated overview ofers, for the irst time in the past century, a compilation of the names of distinguished university students who throughout their studies attained top grades and hereby proved worthy of the acknowledgement of the head of state in the form of an Honour Doctoral Awarding Ceremony. A brief outline of the prehistory of honour doctoral awards is followed by an overview of the varied history of distinguished promotio in Hungary and in Debrecen (promotio sub auspiciis Regis, promotio sub auspi ciis Gubernatoris, promotio sub laurea Almae matris, promotio sub auspiciis Rei Publicae Popularis, promotio sub auspiccis Praesidentis Rei Publicae), which is supplemented with a survey of legal and regulatory dispositions. Finally we are given an opportunity to get acquainted with the names of distinguished honour doctors. An equally valuable part of the disquisition is a compilation of pictorial material representinglashes of rare moments.